2020
DOI: 10.3389/fncel.2020.544431
|View full text |Cite
|
Sign up to set email alerts
|

TSPO Ligands PK11195 and Midazolam Reduce NLRP3 Inflammasome Activation and Proinflammatory Cytokine Release in BV-2 Cells

Abstract: Neuroinflammation related to microglial activation plays an important role in neurodegenerative diseases. Translocator protein 18 kDa (TSPO), a biomarker of reactive gliosis, its ligands can reduce neuroinflammation and can be used to treat neurodegenerative diseases. Therefore, we explored whether TSPO ligands exert an anti-inflammatory effect by affecting the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, thereby inhibiting the release of inflammatory cytokines in microglial cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Our previous studies have shown that TSPO ligands PK11195 and Midazolam have potential therapeutic effects on neuroinflammation [ 21 ]. In the current study, we investigate the antineuroinflammatory effects and possible mechanisms of PK11195 and Midazolam in LPS-activated BV-2 microglia cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that TSPO ligands PK11195 and Midazolam have potential therapeutic effects on neuroinflammation [ 21 ]. In the current study, we investigate the antineuroinflammatory effects and possible mechanisms of PK11195 and Midazolam in LPS-activated BV-2 microglia cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Researches over the last few decades have had a strong emphasis on the interaction of TSPO with its ligands, the most common of which is PK11195 12 .TSPO ligands have shown promising therapeutic prospects in various studies [14][15] . Previous studied in our laboratory showed PK11195 and Midazolam have anti-in ammatory action in vitro 21 . Meanwhile, in vivo we found that PK11195 could regulate the process of mitophagy 23 .…”
Section: Discussionmentioning
confidence: 74%
“…Our previous studies have shown that TSPO ligands have potential therapeutic effects on neuroin ammation 21 . In the current study, we go ahead to investigate the anti-neuroin ammatory effects and possible mechanisms of TSPO ligands in LPS-activated BV-2 microglial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Lu et al [26] showed that midazolam can significantly inhibit IL-1β-induced release of IL-6 in rat C6 glioma cells in a concentration-dependent fashion up to inhibition by 43.58% with 3 μM midazolam concentration, while propofol elicited no significant effect on IL-1β-induced the release of IL-6. Recently, Horiguchi et al [34] and Feng et al [35] experimentally reported that midazolam pretreatment suppressed LPS-induced the upregulation of the costimulatory molecule CD80 and the release of IL-6 and NO in peripheral monocyte-derived macrophages with the suppression of the activation of NF-κB and mitogenactivated protein kinase in human cells.…”
Section: Discussionmentioning
confidence: 99%